We Don't need Another Hero. 10th Berlin Biennale for Contemporary Art. - Ngcobo, Gabi; Schriber, Abbe; Williams, Alena; Diallo, AÏcha; Elliott, Beth; Wainaina, Binyavanga; Madono's, Bongani; Dakin, Dagara; King, Daniella Rose; Lopes, Fabiana; Menezes, Hélio; Rjeille, Isabella; et al. (Distanz Verlag : Berlijn, 2018)
Yiadom-Boakye, Lynette ; Pfeifer, Mario ; Thompson, Mildred ; Cherono Ng'ok, Mimi ; Biabiany, Minia ; Lange, Moshekwa ; A. Kelly, Natasha ; Okpokwaili, Okwui ; Murillo, Oscar ; Altin, özlem ; Belli, Patricia ; Zvavahera, Portia ; Samiee, sam ; Haq, sara ; Leigh, Simone ; Twalo, Sinetghemba ; Arnell, Jabu ; Perry, Sondra ; Mars, Tessa ; Oussou, Thierry ; Cokes, Tony ; Cruz Pabon, Tony ; Chaudhari, Zuleikha ; Brzezanska, Agnieszka ; Mendieta, Ana ; Mahmood, Basir ; Ayon, Belkis ; Marcelle, Cinthia ; Seshee Bopape, Dineo ; M'bala, Els ; Wolukau-Wanambwa, Emma, Faleiros, Fabiana ; Baez, Firelei ; Nkosi, Gabisile ; Kilomba, Grada ; Amin, Heba Y. ; Mbamba, herman ; Piotrowska, Joanna ; Unzueta, Johanna ; Phillips, Julia ; Keleketla!Library ; Las Nietas de Nono ; Johnson Artur, Liz ; Gutierrez Camejo, Lorena ; Himid, Lubaina ; Willis Thompson, Luke ; Hamann, Lydia ; Osteroth, Kai
10th Berlin Biennale for Contemporary Art , Kunstwerke, Berlijn, 9 Juni 2018 - 9 September 2018
boek